Local Treatment of Metastatic Prostate Cancer: What is the Evidence So Far?. (19th March 2018) - Leonel Almeida, Pedro; Jorge Pereira, Bruno
Abstract : Background . Advances in technological, laboratorial, and imaging studies and new treatments available in the last decades significantly improved prostate cancer survival rates. However, this did not occur in metastatic prostate cancer (mPCa) at diagnosis which, in young and fit patients, will become invariably resistant to the established treatments. Progression will lead to an impairment in patients' quality of life and disease-related death. Methods . The authors intend to perform a literature review of the advantages of primary treatment of mPCa. Articles were retrieved and filtered for relevance from PubMed, SciELO, and ScienceDirect until March 2017. Results . Primary treatment is currently indicated only in cases of nonmetastatic PCa. Nonetheless, there might be some benefits in doing local treatment in mPCa in order to control local disease, prevent new metastasis, and improve the efficacy of chemotherapy and hormonotherapy with similar complications rate when compared to locally confined cancer. Independent factors that have a negative influence are age above 70 years, cT4 stage or high-grade disease, P S A ≥ 20 ng/ml, and pelvic lymphadenopathies. The presence of 3 or more of these factors conditions CSS and OS is the same between patients who performed local treatment and those who did not. Metastasis degree and location number can also influence outcome. Meanwhile, patients with visceral metastases have worse results. Conclusions . There is growing evidence supporting local treatment in cases of metastatic prostate cancer at diagnosis in the context of a multimodal approach. However, it should be kept in mind that most of the existing studies are retrospective and it would be important to make consistent prospective studies with well-defined patient selection criteria in order to sustain the existing data and understand the main indications to select patients and perform primary treatment in mPCa.